2021
DOI: 10.21037/hbsn.2020.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on hepatocellular carcinoma recurrence after liver transplantation through long-term follow-up

Abstract: Background: Obesity is associated with increased oncological risk and outcomes but the evidence surrounding the effect of body mass index (BMI) on increased risk of hepatocellular carcinoma (HCC) recurrence after liver transplantation (LT) is still questionable. The purpose of this retrospective study of a large cohort of adult patients transplanted for HCC was to investigate the effect of BMI on the incidence of HCC recurrence and outcome.Methods: Data from 427 adult recipients transplanted for HCC between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Data from prior studies is conflicting; some previous studies with smaller patient cohorts have shown an association with higher BMI and diabetes and increased risk of post-LT HCC recurrence as well as decreased survival post-transplantation 33–36. The most recent and largest study prior to ours found that BMI at time of transplantation did not impact post-LT HCC recurrence nor long-term survival 37. It is clear that future studies using large datasets will be helpful to continue to explore the impact of these features on risk for HCC recurrence.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Data from prior studies is conflicting; some previous studies with smaller patient cohorts have shown an association with higher BMI and diabetes and increased risk of post-LT HCC recurrence as well as decreased survival post-transplantation 33–36. The most recent and largest study prior to ours found that BMI at time of transplantation did not impact post-LT HCC recurrence nor long-term survival 37. It is clear that future studies using large datasets will be helpful to continue to explore the impact of these features on risk for HCC recurrence.…”
Section: Discussionmentioning
confidence: 55%
“…[33][34][35][36] The most recent and largest study prior to ours found that BMI at time of transplantation did not impact post-LT HCC recurrence nor long-term survival. [37] It is clear that future studies using large datasets will be helpful to continue to explore the impact of these features on risk for HCC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC), the most common form of primary liver cancer, ranks among the deadliest malignant tumors affecting humans (1,2). Major risk factors for HCC include hepatitis B (HBV) and hepatitis C (HCV) infections, excessive alcohol consumption, smoking, obesity, diabetes, and other metabolic disorders (3)(4)(5). Recent studies have highlighted that over 40% of new liver cancer cases worldwide are diagnosed in China (6).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) as the most frequently occurring type of primary liver cancer is one of the most lethal human malignant tumors (1,2). Major risk factors of HCC include infections with hepatitis B (HBV), hepatitis C (HCV), excess alcohol intake, smoking, obesity, diabetes and other metabolic diseases (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%